Upper Digestive Endoscopic Findings in Patients with Chronic Renal Insufficiency in Phase of Dialysis - Marcos Félix Osorio Pagola; David Rodríguez Zamora; Juan Luís de Pasos Carrazana; Libán Álvarez Cáceres; Orelvis Martínez Martínez; Anagalys Ortega Alvelay (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: Patients with chronic renal insufficiency in phase of dialysis present clinical manifestations that can include different symptoms. Morbidity due to gastric, esophageal and duodenal disturbances is significant and constitutes a considerable risk before, while and after a renal transplant. Objective: To identify the most frequent disturbances of the upper digestive tract in patients with chronic renal insufficiency who require dialysis. Methods: An observational, descriptive and retrospective study was carried out in this search. The universe was composed by all the patients with a diagnosis of chronic renal insufficiency in a dialysis phase, who had been included in the Hemodialysis Program at the University Hospital "Dr. Gustavo Aldereguía Lima" from Cienfuegos and who had undergone an upper digestive endoscopy from January to May, 2008. The patient's health record was studied to get information for the variables under study. Results: the average age was 46,7 years and the most affected patients were males. The mean value for serum creatinine was 929,7 mMol/L, for serum urea 21,4 mMol/L and for hemoglobin 8,4 g/L. The most frequent cause of chronic nephropathy was High Blood Pressure in 25 patients (56,8 %), followed by Diabetes Mellitus in 9 patients (20,5 %). 52,3 % of the patients were asymptomatic, but the most frequent symptoms reported by the patients were flatulence (25 %) and nausea (15,9 %). Endoscopy revealed normal results in most of the patients (40,9 %). Conclusions: Antral erythematous endoscopic gastritis was the most frequent endoscopic diagnosis followed by duodenal ulcer